2010
DOI: 10.1016/s0074-7750(10)39004-5
|View full text |Cite
|
Sign up to set email alerts
|

Health Conditions Associated with Aging and End of Life of Adults with Down Syndrome

Abstract: Expectations for the life course of individuals with Down syndrome (DS) have changed, with life expectancy estimates increasing from 12 in 1949 to nearly 60 years of age today (Bittles & Glasson, 2004;Penrose, 1949). Along with this longer life expectancy comes a larger population of adults with DS who display premature age-related changes in their health. There is thus a need to provide specialized health care to this aging population of adults with DS who are at high risk for some conditions and at lower ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
120
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 106 publications
(171 reference statements)
4
120
1
2
Order By: Relevance
“…17 Comparing to these studies, we found lower rates of osteoporosis (1.7%), obesity (2.3%) and skin conditions (1.1%). DS adults seem to be at lower risk for malignant solid tumours 29 than the general population. In fact, none of our DS patients had been diagnosed with cancer malignancy.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…17 Comparing to these studies, we found lower rates of osteoporosis (1.7%), obesity (2.3%) and skin conditions (1.1%). DS adults seem to be at lower risk for malignant solid tumours 29 than the general population. In fact, none of our DS patients had been diagnosed with cancer malignancy.…”
mentioning
confidence: 83%
“…14,17,28 Other studies have described additional medical issues in DS adults, including skin and hair diseases, early-onset menopause, visual and hearing impairments, pulmonary disease, obstructive sleep apnoea, musculoskeletal disease, type 1 diabetes mellitus, overweight and obesity, gastroesophageal reflux disease, celiac disease and an age-related increased risk for dementia. 14,17,[25][26][27]29,30 The likelihood of epilepsy and seizures increases with age, especially if there is comorbid dementia, but is also related to the age of onset of the disease. 29 In some studies, older adults with DS were found to have a higher incidence of respiratory disease and congenital anomalies, 29 dementia, hypothyroidism, skin problems, 17 cardiac disease, neurologic disease as well as shorter height and stature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A hallás csökkenése, a cataracta kialakulá-sa, az atlantoaxialis gerincinstabilitás is jelentős lehet 30 éves kor előtt, és már ekkor elkezdődhet és fokozódhat a pszichomotoros retardáció és az Alzheimer-kór is. Esbensen [12] vizsgálatai szerint előtérbe kerülnek a bőr-és hajelváltozások, a korai menopauza lehetősége, az epilepsziakészség, a hypothyreosis, a diabetes, az obesitas, az alvási apnoe és a gerincterhelhetőségi problémák.…”
Section: Eredeti Közleményunclassified
“…Anwar, Walker, and Frier (1998) found that Type I diabetes occurs at a rate of 1.4-10.6% of individuals with DS in an area of Scotland, while the estimated incidence of Type 1 diabetes was 0.18-.3% in the general population of the United Kingdom. Individuals with DS do not appear to be at an increased risk of Type 2 diabetes (Esbensen, 2010). In a study of 440 children with DS, 0.9% of their parents reported diabetes (Roizen et al, 2013); however the occurrence of diabetes was not specified as Type 1 or Type 2.…”
Section: Health Problems Of Individuals With Down Syndromementioning
confidence: 99%